Curcumin Restrains Oxidative Stress of After Intracerebral Hemorrhage in Rat by Activating the Nrf2/HO-1 Pathway - Duan, Chenyang; Wang, Hanbin; Jiao, Dian; Geng, Yanqin; Wu, Qiaoli; Yan, Hua; Li, Chunhui (Frontiers in Pharmacology, 2022)
Intracerebral hemorrhage (ICH), a severe hemorrhagic stroke, induces cerebral oxidative stress and severe secondary neurological injured. Curcumin was demonstrated that inhibit oxidative stress in the brain after ICH. However, the pharmacological mechanism needs further research. We used an intrastriatal injection of autologous blood to make the rat ICH model, and then the rat treated it with curcumin (100mg/kg/d). mNSS score and corner test results showed that curcumin could significantly promote the neurological recovery of ICH rats. Meanwhile, curcumin could substantially reduce ROS and MDA in the tissues around intracranial hematoma and prevent GSH depletion. To explore the pharmacological molecular mechanism of curcumin, We used HAPI cells and primary rat cortical microglia for in vitro experiments. In vitro, heme-treated cells were used as the cell model of ICH to explore the molecular mechanism of inhibiting oxidative stress by curcumin treatment. The results showed that curcumin significantly inhibited Heme-induced oxidative stress, decreased intracellular ROS and MDA, and promoted Nrf2 and its downstream antioxidant genes (HO-1, NQO1, and Gpx4) expression. These results suggest that curcumin inhibits oxidative stress by activating Nrf2/HO-1 pathway. Here, our results indicate that curcumin can promote the inhibition of oxidative stress in microglia by activating the Nrf2/HO-1 pathway and promoting neurological recovery after ICH, providing a new therapeutic target for clinical treatment ICH.